A Web-based Model for TEFL and its Effectiveness in Developing Students' Learning: A Research and Development Study at Private Junior High Schools in Bandung. - Jati, A Gumawang (2010)
The purpose of this study is to construct an appropriate Web-based Model for the Teaching of English as a Foreign Language (TEFL) and assess its effectiveness in developing students' learning for the Junior High School in Indonesia. The Web-based Model designed was discussed along with its features and learning management systems. The Web-based Model for TEFL consists of three zones. Zone 1 (input) in the model is guided by behaviorist learning theories to introduce new language items. Behaviorist stresses on practice and drill (Gillani, 2003). Zone 2 (exposure) is guided by cognitive learning theories where the students are exposed to authentic materials followed by Tasks. In doing the task, students have to collaborate with their friends and teacher. This kind of activity facilitates knowledge construction (Murphy & Cifuentes, 2001). Zone 3 (practice) is guided by social learning theories where the students have the opportunity to apply their knowledge and skills gain from zone 1 and 2. Social environment facilitated by website medium encourages students to have meaningful communication (Gillani, 1998). The design of this study is research and development (Borg, 1979) which has a number of major steps and cycle. They are (1) research and information collecting, (2) planning, (3) development of preliminary form of Web-based Model for TEFL, (4) preliminary field testing, (5) main Web-based Model for TEFL development, and (6) main field testing. There were 4 instruments used in this study, i.e. questionnaire, interview guides, observational sheets, and test. Data from questionnaire, interviews, and observations were analyzed qualitatively. The analysis shows that the Web-based Model for TEFL facilitates the teaching and learning process. The students responded that the authentic learning materials and activities in the three zones of the Web-based Model for TEFL encourage them to work collaboratively. They also found that the learning activities and tasks are useful. It can be concluded that the Web-based Model for TEFL facilitates the teaching and learning process and the model can be used to develop teaching and learning for other subjects at junior and senior high schools in Indonesia. Data from the test results were analyzed using inferential statistics to examine whether the experiment and control groups perform differently in the tests. The analysis shows that the experimental groups scored higher than the control groups. There were some limitations when this study was conducted such as problems during the treatment, accessing materials and observation. The limited time available for training the teachers about Learning Management System caused some minor problems during the treatment, for example login, uploading task, scoring and giving feedback . Some learning materials, especially videos could not be accessed by more than 10 students at the same time. Students' learning activities in the control groups were not observed and could not be reported in this study.